PENGARUH KINERJA LINGKUNGAN DAN PENGUNGKAPAN INFORMASI LINGKUNGAN TERHADAP KINERJA EKONOMI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - lusiana, Lusiana; Angelia, Angelia (Universitas Putra Indonesia YPTK Padang, 2015)
AbstractThis study aims to look at the Effect of Environmental Performance and EnvironmentalDisclosure Against Economic Performance. Methods of data collection, the authors use apurposive sampling while the analysis is a simple regression analysis and multiple regression.My recommendation for the company to be more active in order to improve itsenvironmental performance assessment to get the best ratings, so it can also improve thecompany's financial performance. Disclose information in a corporate environment, companiesbetter explain its disclosure with greater clarity or detail that the information provided mayhelp researchers more clearly.Keywords: Environmental Performance,Environmental Disclosure, Economic Performance